Bridging the spatiotemporal scales of macromolecular transport in crowded biomimetic systems. Issue 6 (13th December 2018) - Regan, Kathryn; Wulstein, Devynn; Rasmussen, Hannah; McGorty, Ryan; Robertson-Anderson, Rae M.
Abstract : We combine single-molecule conformational tracking with digital Fourier microscopy to couple crowding-induced conformations and trajectories of single molecules with ensemble-averaged transport properties across an unprecedented spatiotemporal range to elucidate the complex dynamics of large DNA crowded by custom-designed networks of actin and microtubules. Abstract : Crowding plays a key role in the transport and conformations of biological macromolecules. Gene therapy, viral infection, and transfection require DNA to traverse the crowded cytoplasm, including the cytoskeletal network of filamentous proteins. Given the complexity of cellular crowding, the dynamics of biological molecules can be highly dependent on the spatiotemporal scale probed. We present a powerful platform that spans molecular and cellular scales by coupling single-molecule conformational tracking (SMCT) and selective-plane illumination differential dynamic microscopy (SPIDDM). We elucidate the transport and conformational properties of large DNA, crowded by custom-designed networks of actin and microtubules, to link single-molecule conformations with ensemble DNA transport and cytoskeleton structure. We show that actin crowding leads to DNA compaction and suppression of fluctuations, combined with subdiffusion and heterogeneous transport, whereas microtubules have much more subdued impact across all scales. In composite networks of both filaments, scale-dependent effects emerge such that actin dictates ensemble DNA transport while microtubules influence single-molecule dynamics. We show that these intriguing results arise from a complex interplay between network rigidity, mesh size, filament concentration, and DNA size.